For White Social Workers: RE/UN/DIScover Heuristic for Dual Awareness in Ongoing Anti-Racist Practice - Keenan, Elizabeth (Advances in Social Work, 2023)
Although many White social workers engage in ongoing anti-racist actions, they may still be complicit in perpetuating and reinforcing racism and White Supremacy Culture. Black, Indigenous, and People of Color (BIPOC) social workers, activists, and scholars have described the numerous ways in which the harmful impacts of White Supremacy Culture appear in the well-intentioned efforts of White people who seek to be anti-racist. White social workers are thus responsible for engaging in intentional ongoing practices to identify, interrupt, and shift their interpersonal oppressive uses of power in their practice. The RE/UN/DIScover heuristic is an iterative, embodied set of three practices for working with one’s experiences of shame and internalized dominance, habitual not-seeing, and in-the-moment activations. Literature theorizing White Supremacy ideology and culture frames the description of the RE/UN/DIScover heuristic. This paper describes several heuristic applications, including prompts for engaging in REcover, UNcover and DIScover practices and two composite examples. These applications illustrate how to use the heuristic practices with dual awareness of self and one’s social work practice in the moment and over time. White social workers are encouraged to learn and use the RE/UN/DIScover heuristic practices to guide their efforts to more fully live into their anti-racist commitments in moments of not-seeing and moments of activation.
Keywords: Heuristic; Power; Social work practice; White social workers; anti-racist; dept.swk; peer-reviewed

The roots of social work practice - Tomczak, Stephen Monroe; Cross-Denny, Bronwyn (Health Science Faculty Publications, 2023)
Keywords: dept.swk

Book Review: Refusal to Eat: A Century of Prison Hunger Strikes - Smoyer, Amy B. (Punishment & Society, 2023)
Keywords: book.review; dept.swk

In the Meantime: RE/UN/DIScover Heuristic for Small-Scale Antioppressive Action within Systems and Organizations - Keenan, Elizabeth King (Social Work, 2023)
The dehumanizing effects of neoliberal, white dominant regulations, laws, policies, and cultural assumptions seep into the everyday practice of social workers in frontline and mid-level positions. Many social workers are learning various antioppressive practices and becoming aware of how microaggressions and other oppressive dynamics can manifest in workplaces but lack models to guide efforts for small-scale action. This article describes how the RE/UN/DIScover heuristic can be used to interrupt and shift oppressive processes during everyday moments of practice within organizations and systems by social workers and their interested colleagues who have some awareness of oppressive and antioppressive dynamics. The RE/UN/DIScover heuristic is an iterative set of three practices: (1) tend to self with compassionate REcover practices; (2) engage in curious, critical reflection to UNcover full understandings of the power dynamics, impacts, and meanings of specific challenges; and (3) DIScover and try out just, humanizing responses with creative courage, individually and with other colleagues. The heuristic uses a dual focus on self and situation with an ad hoc group of other colleagues to raise awareness; cultivate humanizing spaces; and implement antioppressive, relational responses. The article describes the heuristic practices and how to apply the heuristic with two composite practice applications.
Keywords: dept.swk; peer-reviewed

RE/UN/DIScover Heuristic: Working with Clinical Practice Impingements in Dehumanizing Times - Keenan, Elizabeth King (Clinical Social Work Journal, 2023)
Although clinical social work seeks to center the transformative potential of human relationships, practitioners are experiencing heightened systemic and organizational impingements from the dehumanizing pressures of neoliberalism. Neoliberalism and racism diminish the vitality and transformative potential of human relationships, disproportionately affecting Black, Indigenous and People of Color (BIPOC) communities. Practitioners are also experiencing increased stress and burnout related to increased caseloads and decreased professional autonomy and organizational practitioner support. Holistic, culturally responsive, and anti-oppressive processes seek to counter these oppressive forces but need further development to synthesize antioppressive structural understandings with embodied relational interactions. Practitioners can potentially contribute to efforts that apply critical theories and antioppressive understandings within their practice and workplace. Through an iterative flow of three sets of practices, the RE/UN/DIScover heuristic supports practitioners’ efforts to respond in those challenging everyday moments where oppressive forms of power are imposed and embedded within systemic processes. With themselves and other colleagues, practitioners engage in compassionate REcover practices; use curious, critical reflection to UNcover full understandings of power dynamics, impacts, and meanings; and draw on creative courage to DIScover and enact socially just and humanizing responses. This paper describes how practitioners can use the RE/UN/DIScover heuristic in two common challenging moments of clinical practice: systemic practice impingements and implementing a new training or practice model. The heuristic seeks to support practitioners’ efforts to preserve and expand socially just, relational spaces for themselves and those with whom they work within the context of systemic dehumanizing neoliberal forces.
Keywords: Clinical practice; Heuristic; Neoliberalism; Power; Practice challenges; Window of tolerance; dept.swk; peer-reviewed

Book Review: Invisible Mothers: Unseen Yet Hypervisible After Incarceration by Garcia-Hallett, J. - Smoyer, Amy B. (Affilia, 2023)
Keywords: book.review; dept.swk

“Sports! More than just a game” - Smith, Christina (Connecticut history, 2023)
Keywords: dept.swk

Building or Burning: Critical Reflections on Social and Political Change - Krings, Amy; D’Angelo, Karen; Ivery, Jan M.; Murphy-Nugen, Amy B. (Journal of Policy Practice and Research, 2023)
Keywords: dept.swk; peer-reviewed

Macro-Level Social Work Interventions in Schools: Poverty Simulation Programs as Professional Development Opportunities for K–12 Educators - Curry, Anna Maria T.; Tomczak, Stephen Monroe (Children & Schools, 2023)
Keywords: dept.swk

Preface - Logan, Isabel; Green, Cheryl (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Keywords: dept.nur; dept.swk

911: Stabilization approaches used by police social workers - Logan, Isabel; Madden, Robert; Sallaku, Katherine (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Police social workers are crucial components of police departments when individuals or communities experience crises. They perform essential tasks, including well-being checks, crisis intervention, de-escalation, mediation, safety planning, referrals to community services, and other preventative measures to stabilize clients in crisis. The chapter will define police social work and give the reader insight into the stabilization approaches used by police social workers to prepare clients for their next level of care. The chapter begins with a brief history of the evolution of police social workers within the context of public policy and their most recent call to action to address mental health crises. The authors utilize a multi-tier approach to highlight stabilization approaches used by police social workers with a focus on empowering individuals, families, and communities to collaborate on solutions. The chapter uses case scenarios drawn from the experiences of police social workers and interns to demonstrate stabilization approaches. A racial equity, culturally responsive, and trauma-informed lens informs the approach to stabilizing client systems in law enforcement settings. © 2023, IGI Global. All rights reserved.
Keywords: dept.swk

The influence of spirituality on professional identity, role performance, and career resilience among nursing home social workers - Rogers, Robin K.; Myers, Dennis R.; Garrison, Brianna V.; Singletary, Jon E.; McClellan, Angela (Journal of Gerontological Social Work, 2023)
This paper explores how social workers integrate personal spirituality within nursing homes, where a highly regulated, stressful environment marginalizes professional identity and challenges retention. Researchers offer new evidence of how spirituality informs professional identity, ethical practice, and continuation in the role. Twenty BSW/MSW licensed nursing home social workers (NHSWs) reported how they daily navigate the personal spirituality-at-work opportunity and challenge. Qualitative analysis of in-depth interviews resulted in three primary codes and related subcodes: Spirituality-Integrated Professional Identity (Vocational Affirmation and Value Alignment), Spirituality-Informed Practice (Intervention Asset, Relational Affinity, and Ambiguous Boundaries), and Spiritually-Sustained Career Resilience. Respondents reported how spirituality animated professional identity, informed daily role enactment, and sustained role involvement. Recommendations are provided for normalizing ethical spirituality-at-work through social work education and practical guidance in navigating the spirituality and practice space.
Keywords: Nursing Home; dept.swk; peer-reviewed; spirituality

Origins of Social Group Work; Special Issue of Social Work With Groups, Volume 46, Issue 4. - Gardella, Lorrie Greenhouse (Taylor and Francis, 2023)
Keywords: dept.swk

Stabilization approaches that empower clients through mental health crises - Logan, Isabel; Green, Cheryl A. (IGI Global, 2023)
Mental health practitioners often overlook initial stabilization strategies and interventions when providing evidence-informed approaches in order to get to the so-called “important” or “interesting” part of treatment. For many mental health practitioners, the “important” or “interesting” component...
Keywords: dept.nur; dept.swk

Snow Day - Gardella, Lorrie Greenhouse (Washing Lines of the World, 2023)
Keywords: dept.swk

Preparing social workers for emerging roles in police social work - Logan, Isabel; Madden, Robert; Solak, Matthew (Journal of Social Work Education, 2023)
Schools of social work must prepare social workers to meet the demands of the rapidly emerging field of police social work. This article reports on the experiences of a social work program’s partnership with a police department. The authors identify an integrative practice model of police social work, specifying social work roles at the baccalaureate and graduate levels, as well as ethical issues. The model is based on the social work competencies and law enforcement best practices. The authors analyze the experiences of placing students directly into law enforcement settings and make recommendations to create successful experiences for students, social workers, and police. The importance of strategic partnerships, communication, trust, and support in building strong relationships is also highlighted.
Keywords: dept.swk; peer-reviewed

Leading in color in academia: a latinx chair’s experience of resiliency and hope - Reyes, Loida (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
On Wednesday, January 20, 2021, Kamala Harris broke through the gender and racial barrier that has kept men at the top ranks of American politics for over two centuries. This moment singlehandedly challenged the definition of leadership and who “fits” in that traditional model. Reyes examines the challenges and highlights three lessons of leading in color in academia today, being the first Latina to chair her department. Her journey reflects similar experiences of women of color who are burdened by the emotional toll that comes with being a part of systemic change, by virtue of leading while of color. To begin dismantling systemic racism and sexism, organizations must commit to addressing the issues head-on by reexamining policies, practices, and work environments that have perpetuated systemic inequalities. Greater supports are needed for women of color to be effective as their contributions are invaluable in achieving true systemic change.
Keywords: Academia; Hope; Latinx experiences; Resiliency; dept.swk

Trusted residents and housing assistance to decrease violence exposure in New Haven (TRUE HAVEN): a strengths-based and community-driven stepped-wedge intervention to reduce gun violence - Tong, Guangyu; Spell, Virginia T.; Horton, Nadine; Thornhill, Thomas; Keene, Danya; Montgomery, Christine; Spiegelman, Donna; Wang, Emily A.; Roy, Brita (BMC Public Health, 2023)
We describe the rationale and study design for “TRUsted rEsidents and Housing Assistance to decrease Violence Exposure in New Haven (TRUE HAVEN),” a prospective type 1 hybrid effectiveness/implementation study of a multi-level intervention using a stepped wedge design. TRUE HAVEN aims to lower rates of community gun violence by fostering the stability, wealth, and well-being of individuals and families directly impacted by incarceration through the provision of stable housing and by breaking the cycle of trauma.
Keywords: Collective wellbeing; Community-based intervention; Gun violence; Housing stability; Incarcerated population; Learn as you go; Multi-component implementation; Stepped wedge design; Structural racism; dept.swk; peer-reviewed

Group well-child care as a facilitator of psychoeducation: pediatrics residents’ perspectives - Nogelo, Patricia Faraone; Oldfield, Benjamin J; Fenick, Ada M; Rosenthal, Marjorie S (Health Education Research, 2023)
Psychoeducation, where clinicians teach problem-solving skills in a supportive environment, can help address families’ social vulnerabilities and promote well-being. Group well-child care (GWCC) may provide unique opportunities for pediatric residents to improve their skills in psychoeducation. Our aim was to characterize pediatric residents’ perspectives and experiences of communication while conducting both individual well-child care and GWCC. We used a longitudinal qualitative study design to conduct 15 semistructured interviews with five pediatric residents who facilitated GWCC. Using the constant comparative method, we characterized pediatric residents’ perspectives and experiences of communication while conducting both individual well-child care and GWCC. Four themes emerged. Residents perceived that GWCC (i) enabled families to honestly share their knowledge and parenting practices, (ii) allowed time and a space for families to share personal stories and scenarios, (iii) facilitated discussions of maternal health and psychosocial matters, toward which residents felt ambivalence, and (iv) fostered skills in psychoeducation that transferred to the rest of their clinical practice. When pediatric residents lead GWCC, they perceive that they can facilitate key aspects of psychoeducation, enabling them to assist families in meeting complex social needs. Residents describe that they transfer psychoeducation skills learned in GWCC to the rest of their practice.
Keywords: dept.swk; peer-reviewed

Negotiating toilet access: a qualitative exploration of women's incarceration - Smoyer, Amy B.; Schwarz, Paige; Camenga, Deepa; Rickey, Leslie (The Prison Journal, 2023)
Norms and behaviors about toileting in prison can expand understanding of women's lived experience of incarceration. Knowledge about this subject is significant because access to clean, safe toilets is a human rights issue, and toilet habits can impact social, mental, and physical outcomes. Three focus groups were conducted with 15 incarcerated women about their quotidian prison toilet experiences. While the toilet was physically available, institutional regulations, social norms, and women's individual psychologies limited their access and utilization. The ways in which toilet use was negotiated with self, peers, and are described, and the implications of these findings are discussed.
Keywords: dept.swk; peer-reviewed

Addressing America's Mental Health Crisis in Public Education - Albee, Laura Jane (Perspectives and Considerations on Navigating the Mental Healthcare System, 2023)
Nearly eight million American youth between the ages of 3 - 17 live with a psychiatric or behavioral health disorder. Many in grades K-12 are being unfavorably impacted in the classroom because of socioeconomic and environmental factors that include poverty, addiction, incarceration, trauma, domesti...
Keywords: dept.swk; peer-reviewed

Humans peeing: Justice-involved women’s access to toilets in public spaces - Smoyer, Amy B.; Pittman, Adam; Borzillo, Peter (PLOS ONE, 2023)
Justice-involved women face myriad challenges as they negotiate the terms of community supervision and manage the long-term implications and stigma of living with a criminal record. Major tasks that women juggle include securing safe, affordable housing, finding and retaining employment, accessing physical and mental health care (including substance use treatment), and handling relationships with family, friends, children, and intimate partners. In addition to these responsibilities, women must meet their basic physiological needs to eat, sleep, and use the toilet. Women’s ability to safely meet their personal care needs may impact their capacity to manage their criminal-legal challenges. This study uses qualitative methods to understand justice-involved women’s lived experiences related to urination. Specifically, the study reports on a thematic analysis of 8 focus groups conducted with justice-involved women (n = 58) and the results of a toilet audit conducted in the downtown areas of the small city in the United States where the focus group participants were living. Findings suggest that women had limited access to restrooms and reported urinating outside. Lack of restroom access impacted their engagement with social services support and employment and their ability to travel through public spaces. Women perceived their public toilet options as unsafe, increasing their sense of vulnerability and reinforcing the idea that they did not have full access to citizenship in the community because of their criminal-legal involvement. The exclusion and denial of women’s humanity that is perpetuated by a lack of public toilet access impacts women’s psychosocial outcomes. City governments, social service agencies, and employers are encouraged to consider how lack of toilet access may impact their public safety and criminal-legal objectives and expand opportunities for people to access safe restroom facilities.
Keywords: Bladder; Employment; Jobs; Mental health and psychiatry; Prisons; Sexual and gender issues; Urban areas; Urination; dept.swk; peer-reviewed

Origins of social group work: local stories from around the world - Gardella, Lorrie Greenhouse (Social Work With Groups, 2023)
Keywords: dept.swk; peer-reviewed